Developing Digital Module for Assisting the Seventh Grade Students to Write Descriptive Texts Easily - Retno Firiani; Dian Fadhilawati (Universitas Islam Balitar, 2022)
This Research and development are intended to establish the digital module for helping the seventh-grade students to write descriptive text easily, to find out the validity of the digital module for assisting the seventh-grade students to write descriptive text as well as to investigate the teachers’ and students’ responses toward the developed digital module for writing descriptive text instruction. This study adapted Sugiyono's concepts which cover: analyzing potentials, problems and solutions, Design and development, Experts Validation and revision, Teachers’ and students’ perception, evaluation and revision, and Final product and publication. The results of this research revealed that 1) the developed digital module consisted of six units: 1) Introduction of Descriptive Text, 2) Let's Learn Vocabulary of Descriptive Text, 3) Let's Learn Grammar for Writing Descriptive Text, 4) Process of Writing Descriptive Text, 5 Let's Practice of Writing Descriptive Text, and 6) Evaluation. Furthermore, the digital module was also completed with worksheets, and manual guidelines for teachers and students, (2) The developed digital module was valid, as shown by the result of the average of the experts’ material validation =93, 3% (very valid), and the average result of media experts’ validation = 88, 9% (very valid), and (3) The developed digital module for learning writing of descriptive text got positive responses from teachers and students. It was supported by the result of the questionnaire given to the teachers = 86, 49% (very good) and the students = 87, 15% (very good). From the result above it is suggested for the teachers to apply this developed digital module as supplementary materials to complete the book provided by the government.